NILAI PENDIDIKAN SOSIAL DAN SOLIDARITAS SOSIAL PADA TRADISI PONAN (STUDI DI DESA POTO DAN BERARE KECAMATAN MOYO HILIR KABUPATEN SUMBAWA) - Merdita, Rita; Syafruddin; Suud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to identify and analyze the value of social education and the value of social solidarity in the Ponan tradition in Poto and Berare Villages, Moyo Hilir District, Sumbawa Regency. This study uses a qualitative approach using ethnographic methods. The types of data used are primary data and secondary data. Data is collected through observation, interviews, documentation, and data is analyzed by means of data reduction, data presentation, and conclusion drawn. The results of this study show that activities in the Ponan tradition have several stages, namely the initial stage such as conducting a meeting to determine the Ponan day and the formation of the Ponan executive committee, making snacks, and preparing the event venue, the implementation stage of the women bringing snacks to the location of Ponan, remarks, chanting prayers, tahlil, tahmid, dhikr and prayers together asking for the salvation of the hereafter and rice plants to avoid disease. the distribution of snacks and eating snacks together, the closing stage of giving rice medicine from Ponan snack leaf waste in the rice fields around the Ponan location and the hospitality of the residents. The Ponan tradition in Poto and Berare Villages has social education values, namely: 1) service, namely community use garden and rice field products as a form of gratitude to Allah. 2) Please help, namely relatives help provide ingredients to make snacks. Family, namely the attendees followed the hospitality of the residents and when they returned home, they were given Ponan snacks. 4) Kettian is praying together. The value of social solidarity in the Ponan tradition is related to mechanical solidarity according to Emile Durkheim, namely: 1) strong collective awareness, namely mutual cooperation at the Ponan location. 2) the normative pattern is to conduct deliberations on the determination of the day of Ponan. 3) low individuality, namely mothers help receive trays and pack snacks.